Computer Network Security 6th International Conference on Mathematical Methods, Models and Architectures for Computer Network Security, MMM-ACNS 2012, St. Petersburg, Russia, October 17-19, 2012. Proceedings - Kotenko, Igor.; Skormin, Victor; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Mathematical Methods, Models, and Architectures for Computer Network Security, MMM-ACNS 2012, held in St. Petersburg, Russia in October 2012. The 14 revised full papers and 8 revised short presentations were carefully reviewed and selected from a total of 44 submissions. The papers are organized in topical sections on applied cryptography and security protocols, access control and information protection, security policies, security event and information management, instrusion prevention, detection and response, anti-malware techniques, security modeling and cloud security.
Finding Malware on a Web Scale. -- Exposing Security Risks for Commercial Mobile Devices -- From Qualitative to Quantitative Enforcement of Security Policy -- Design and Implementation of a Cloud-Based Assured Information Sharing System -- Optimization of Key Distribution Protocols Based on Extractors for Noisy Channels within Active Adversaries -- A Vulnerability in the UMTS and LTE Authentication and Key Agreement Protocols -- Blind 384-bit Digital Signature Scheme -- RABAC: Role-Centric Attribute-Based Access Control -- Trust-Aware RBAC -- Alternative Mechanisms for Information Security -- Flow Policies by a Three-Valued Analysis -- Towards the Orchestration of Secured Services under Non-disclosure Policies -- An Approach for Network Information Flow Analysis for Systems of Embedded Components -- Individual Countermeasure Selection Based on the Return On Response Investment Index -- Security and Reliability Requirements for Advanced Security Event Management -- Model-Based Security Event Management -- Using Behavioral Modeling and Customized Normalcy Profiles as Protection against Targeted Cyber-Attacks -- Limitation of Honeypot/Honeynet Databases to Enhance Alert Correlation -- Stochastic Model of Interaction between Botnets and Distributed Computer Defense Systems -- Malware Characterization Using Behavioral Components -- MADAM: A Multi-level Anomaly Detector for Android Malware -- Using Low-Level Dynamic Attributes for Malware Detection Based on Data Mining Methods -- Configuration-Based Approach to Embedded Device Security -- A Study of Entropy Sources in Cloud Computers: Random Number -- Generation on Cloud Hosts -- Security Modeling of Grid Systems Using Petri Nets -- Using Graph Theory for Cloud System Security Modeling.
Keywords: Computer science; Computer Communication Networks; Computer network architectures; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Computer Science; Systems and Data Security; Computer Communication Networks; Computers and Society; Data Encryption; Operating Systems; Computer System Implementation